Lebesgue inequalities for the greedy algorithm in general bases - Berná, Pablo M.; Blasco, Óscar; Garrigós, Gustavo (Revista matemática complutense, 2017)
We present various estimates for the Lebesgue type inequalities associated with the thresholding greedy algorithm, in the case of general bases in Banach spaces. We show the optimality of the involved constants in some situations. Our results recover and slightly improve various estimates appearing earlier in the literature.